CULTURAL DIVERSITY IN BILINGUAL EDUCATION - Rusmawaty, Desy (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
This article attempts to understand how cultural diversity in bilingual education plays crucial role in the development of students’ cultural identity and self concept. It reveals that cultural diversity should be implemented well in bilingual education to support the metalinguistic skills in processing information through different languages.